Analisa Pengaruh Penggunaan Aplikasi Flip Dalam Layanan Transaksi Transter Antar Bank Menggunakan Metode SEM - Ven Jean, Colonel Caesar Sancho; Sembiring, Sintaria (TeIKa, 2024)
Transfer services represent advancements in banking technology within information systems, significantly enhancing operational efficiency across various domains. This case study delves into the Latte Factor concept within the interbank transfer service, elucidating the accrual of minor expenses that, if overlooked, can markedly diminish daily income. The FLIP application emerges as a pioneering tool providing cost-free inter-bank transfer services. The Structural Equation Modeling (SEM) method serves as the analytical framework, encompassing validity and reliability tests (Measurement Model Analysis), and Path Analysis (Structural Model), aimed at scrutinizing the relationships among variables within the model. The SEM data emanates from 100 respondents utilizing the FLIP application in the Depok area, spanning diverse professions and age groups. With commendable outcomes in terms of data validity, reliability, and path analysis utilizing the SEM method, it can be deduced that the FLIP application exerts a significant influence on users within the interbank transfer system. Consequently, the data results furnish substantive value, affirming the efficacy of the FLIP application in the financial landscape.